Menuju Indonesia Emas: Tantangan, Hambatan, dan Mitigasi atas Fenomena Pemilihan Umum Tahun 2024 - Teguh Purnomo (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
General Elections (Pemilu) are the main foundation in a country's democratic system. However, the integrity and fairness of the election process is often faced with challenges and obstacles that affect legitimacy and public trust. This research aims to identify challenges, obstacles, and mitigation efforts in maintaining the integrity of honest and fair elections in Indonesia. Using a qualitative approach, data was collected through in-depth interviews with five key informants, including Regional KPU Commissioners, Regional Bawaslu Commissioners, Community Leaders, Religious Leaders, and Legislative Candidates. Thematic analysis was conducted to identify patterns and themes that emerged from the data. The findings show that challenges such as money politics, resource disparities, manipulation of information, intimidation and violence are still significant problems in the election process in Indonesia. Barriers to implementing mitigation include limited supervision, involvement of related parties, and inadequate political culture. Recommended mitigation steps include strengthening supervision, political education, strengthening regulations, and community empowerment. This research makes an important contribution to the understanding and improvement of Indonesia's electoral system, as well as encouraging positive change in the country's political process